Development of a Canny House Security via IoT - Siti Farisah Nadiah Amer; Wan Nur Fazliana Alyaa Abd Rahman; Ahmad, Nur Azliza (Multidisciplinary Applied Research and Innovation, 2024)
With the rise of smart homes, security has become a top priority. However, many traditional security systems are limited in their capabilities and often require manual intervention. This project aims to address this issue by developing a smart security system that utilizes IoT technology to provide more efficient and effective security measures. The purpose of this investigation is to address this issue by designing a smart security system that employs IoT technology to deliver more efficient and effective security measures. To allow the door to be opened, the system is improved with a keypad and an ESP32-CAM. This system also employs gas sensors to ensure that the house is constantly in a safe state. Additionally, a notification system is in place to keep homeowners informed about home security via Blynk. The Internet of Things (IoT) plays a significant role in enabling the functioning of the system. The paper illustrates the hardware and software requirements, the methodology used for implementation, and the result and discussions based on testing the system components. The results indicate that the system works well and successfully detects the faces, controls the smart door lock and detects the gasses in the house. The camera detection demonstrates accurate detection with a range of 4 seconds for registered persons, while for the solenoid, the detection for the door opens within a range of 1 second. Based on the result, the ESP32-CAM performs reliably and consistently. The Blynk application is used to provide home security monitoring and control capabilities, whether in monitoring the user’s face or the level of gas security at home. Overall, the Development of a Canny Smart House system is very convenient for the owner, and further improvements will be made based on the test result.